Monitoring dan Evaluasi Pengembangan Kurikulum di SMP Negeri 8 Surabaya - Fauziyah, Hikmatul; Mukhdlor, M.Fatikh; Azahro, Fatimmah; A, Reykha Zatri Putri; Amalia, Kaniati (Lembaga Yasin AlSys, 2024)
The purpose of this research is to find out how the development of the curriculum in a school and what are the obstacles in the implementation of the curriculum. As well as how the evaluation is done in dealing with existing obstacles. This research uses quantitative descriptive methods and literature review systems. The results of this study indicate that the implementation of the curriculum has not been evenly distributed but is going well with the P5 activities.